Usability Analysis of Educational Assistance Information Systems Using the Heuristic Evaluation and End User Computing Satisfaction (EUCS) Methods. - Angel Novita Sinurat; Anggyi Trisnawan Putra (Universitas Negeri Semarang, 2024)
User interface and user satisfaction are crucial components of a system that can significantly impact its usability. SIBADIK, as a web-based application used by many students as a scholarship platform, should have a high level of usability. However, there has been no specific research analyzing the usability of the SIBADIK website. Usability analysis is necessary to determine whether the website is acceptable to users or if there are issues that need to be addressed. The method used is heuristic evaluation combined with End-User Computing Satisfaction (EUCS) to measure user satisfaction levels before and after improvements. The sample was obtained using purposive sampling technique with Slovin formula at 10% margin of error, resulting in 95 samples. The research findings indicate that the SIBADIK website received a user satisfaction score of 2.92 (in the